Antifungal activity of Salacia oblonga extracts Against Human Pathogen Candida albicans - Musini, Anjaneyulu; Pokala, Bhargavi; MD, Zahoorullah.S.; Yeddanapalli, Prathima; Manchella, Jahnavi (International Journal of Scientific Research in Biological Sciences, 2018)
Salacia Oblonga shrub belonging to the family ‘Celestraceae’. It is found in India and Srilanka. We have collected the plant extract from Western Ghats, India. In traditional medicines it is used for the treatment of diabetes and can be exploited to treat many chronic and infectious diseases. The plant extracts of S.oblonga has been used on the treatment of diabetes, polyuria, gonorrhea, rheumatism, asthma and fever. We have undertaken present study to evaluate the antifungal activity of S.oblonga aerial and root extracts against human pathogen Candida albicans. Antifungal activity of methanol extract (1 mg/ml) and ethyl acetate extracts were tested. Extracts have shown good growth inhibition against Candida albicans. Identified the minimum inhibitory concentration of the plant extract 40µg/ml comparison with synthetic drug Clotrimazole 60µg/ml. Separation of the phytochemical from the crude extracts by thin layer chromatography and identified the active fraction. Our study highlighted the antifungal activity of Salacia Oblonga extracts.